Disentangling economic, cultural, and nutritional motives to identify entry points for regulating a wildlife commodity chain. (October 2019) - Bachmann, Mona Estrella; Junker, Jessica; Mundry, Roger; Nielsen, Martin Reinhardt; Haase, Dagmar; Cohen, Heather; Kouassi, Joseph A.K.; Kühl, Hjalmar S.
Abstract: Development of reduction policies for products risking the health or the environment usually begins with the question of whether the most promising entry point is reducing production, distribution or consumption. We aim to answer this crucial question for bushmeat, a wildlife product whose unsustainable harvest threatens biodiversity and food security. We collected one of the largest data sets available on bushmeat commodity chains by interviewing 348 hunters, 202 bushmeat traders, 190 restaurant owners, and 985 consumers in 47 urban and rural settlements around Taï National Park, Côte d'Ivoire. We examined 1) structural traits by network analyses and 2) disentangled the underlying economic, cultural, and nutritional motives for bushmeat utilization at the level of production (hunters), distribution (bushmeat traders), and consumption (households). We found that while economic drivers determined hunting, trading was associated with economic and cultural drivers and consumption was purely influenced by cultural habits. Bushmeat traders were promising candidates for effective regulation interventions, but held a small market share and the risk of displacement to other trading channels remains. Since cultural motives for consumption provide a key opportunity for large-scale behavioral changes, we propose consumers as the most effective point of entry for interventions. However, any such consumer level intervention should be supported by programs providing the remaining commodity chain actors with alternative livelihoods. Generally, interventions into the complex social-ecological system of wildlife commodity chains must consider interdependencies and require multi-actor approaches and monitoring to avoid displacement and diffusion effects and to guarantee a socially and ecologically sustainable change. Highlights: The drivers of bushmeat utilization diverge at each node of the commodity chain. Drivers shift from economic to economic-cultural and cultural between hunting, trading and consumption. Cultural motives for consumption provide a potential entry point for large-scale behavioral shifts. Effective regulation of wildlife commodity chains requires multi-actor approaches.